The Sliding Surface Determination of A Deep-seated Landslide on Cisumdawu Highway, West Java, Based on The Electrical Resistivity Tomography - Santosa, Imam; Sulaksana, Nana; Yuningsih, Euis Tintin; Zakaria, Zufialdi (Indonesian Journal on Geoscience, 2024)
Sumedang is one of the regencies in West Java Province that usually experiences landslides due to its lithology, slopes, and water level conditions. Previously slow-moving landslides occurred between 2016 and February 2021, affected the new Cileunyi-Sumedang-Dawuan (Cisumdawu) Highway at Section 2, Station 21 in the North Sumedang District. This research aims to identify the causes of these landslides using a combination of geological field observation, subsurface geo-electric resistivity-based survey, and borehole drilling. A total of fourteen boreholes were drilled to collect geotechnical data from the subsurface of the researched area, including the soil material and N-SPT value. The soil hardness and resistivity were measured and compared to establish the relationship between resistivity and engineering properties. The result of the resistivity measurement showed that the percolating water zone in the permeable loose soil was located above the impermeable layer, estimated as a slip surface. The subsurface measurement and borehole data show that the lithology of the sliding surface is a layer of clay with a thickness of 5 - 12 m, the slope of the sliding surface is 20o, and the depth is between 24 - 26 m. The cover layer of the sliding surface is a layer of silty clay and gravelly clay with a thickness of 5 - 10 m. Thus, based on the data presented, installation of bore piles and groundwater level monitoring need to be done as mitigation efforts.